Surface properties, micellar molecular interaction, and physical properties for binary systems of sodium oleate with three anionic surfactants. Issue 5 (4th May 2017) - Fu, Lei; Wang, Zhongni; Li, Xuepeng; Zhang, Li
ABSTRACT: The mixed micellization of the anionic surfactant sodium oleate (NaOL) and three anionic surfactants (NaDC, AOT, SDS) of different structures in 0.01 mol/L NaCl solution was investigated by surface tension measurement at different temperatures. All the investigated mixtures exhibited nonideal behaviors as the experimental critical micelle concentration ( CMC ) values were less than the values calculated by using the Clint's equation. Negative β m values calculated by using Rubingh's equation and |ln( CMC 1 / CMC 2 )| < |β m | proved synergism in the three systems of higher αNaOL or lower α NaOL . An interesting phenomenon of double inflection points was observed for pure NaOL and mixtures of high α NaOL . The negative Δ G 0 m values for the mixed systems imply that the micelle formations are spontaneous process. The NaOL/NaDC system was also studied in buffer solution (pH 8, 12) at 30°C which also exhibited nonideal behavior. Synergism existed at pH 12 but not at pH 8 for the NaOL/NaDC system. It is noteworthy that there were no double inflection points for NaOL/NaDC system in buffer solution (pH 8, 12). Krafft point and calcium stability data show that these three anionic surfactants can improve the water solubility and hard-water resistance of soap. GRAPHICAL ABSTRACT: